Ecological Dynamics Approach to Decision Making in Sport. Training Issues (Baltic Journal of Sport and Health Sciences, 2008)
The content of an athlete’s perception during sports practice and the way it determines his / her decisions are some of the key questions in sport and have important consequences on the training process. The decision making in sport (DMS), influenced by cognitivist theories, has been considered until recently as a mere mental process more or less elaborated depending on the practitioner’s level. The current model, conceiving the perception of the environment and the action as separated processes, presents some limitations to explain the creativity, flexibility and adaptability that characterises the athlete behaviour. The juxtaposition of ecological psychology and dynamic systems theory (DST) under the name of ecological dynamics offer an original and alternative perspective to understand DMS. In this way, it appears that a specific mental process to produce the decisions is no longer necessary. The decisions seem to emerge spontaneously out of the nonlinear interaction of the components of the system. The personal, task, and environmental constraints in each specific context organize those components in specific configurations that present decisions of the system. From the new perspective, the decision is fruit of the athlete’s interaction with his / her context. Therefore, the athlete’s function is no longer  act effectively. The paper offers a brief historical outline of the evolution of the concept of DMS, explains the basis and limitations of the cognitivistic model of DMS, develops the DMS from the ecological dynamics perspective — focusing on some main concepts (self-organisation, order and control parameters and phase transitions) and some recent research results in individual and team sports — and finally presents the practical consequences of the new model in the training process at three different levels: personal, task and environmental constraints.Keywords: decision-making in sport, ecological dynamics, dynamic systems theory, sports training.